Implementation of Wallace Tree Multiplier Using 8:4 Compressor (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Multipliers are prime scheme implementation of Microprocessors, VLSI and Embedded Systems. Regrettably, Multipliers are designate by compound function represent and constitute one of the supreme power consuming digital blocks. Estimate computing is an Emerging trend in VLSI design. Now a day the Multiplier is a vital role in most research and development areas. In this paper, the Implementation of Wallace tree Multiplier using 8:4 Compressor is done. The multiplier design will be made by 8:4 Compressor that reduces the power consumption than the optimized compressor design. The proposed 8:4 Compressor is implemented using AND and OR gates.